Scent of a woman - Brest, Martin ([Universal City, CA] : Universal pictures [production company] ; Kuala Lumpur : Berjaya HVN, 1998)
Hoping to earn extra money, an innocent and reserved scholarship student at an exclusive prep school agrees to look after a blind, retired Lieutenant Colonel, who takes him off for a wild weekend in New York City
n.2 is acquisition for KPI (Kelab Pencinta Ilmu)
Executive producer, Ronald L. Schwary ; editor, William Steinkamp, Michael Tronick ; screenplay, Bo Goldman
Cast: Chris O' Donnell
VCD format
Keywords: Man-women relationships in motion pictures; Friendship -- Drama; Blind -- Drama